Analisis Pengendalian Mutu Produk Dupa Cempaka Dengan Pendekatan Statistical Process Control (SPC) Di Perusahaan XYZ - Jaya, Kadek Bagus Putra; Yuarini, Dewa Ayu Anom; Wrasiati, Luh Putu (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2026)
This study aims to identify the factors contributing to product defects in the incense stick production process and to formulate improvement recommendations to effectively reduce the defect rate at XYZ Company. The method used in this research is Statistical Process Control (SPC), a quality control approach that monitors, manages, analyzes, and improves process performance using statistical methods. The data analyzed in this study consist of defective product quantities from the production of Dupa Cempaka during March 2025. The analysis utilizes control charts, histograms, Pareto diagrams, p-charts, flowcharts, and cause-and-effect diagrams. The results indicate three main categories of product defects: breakage, peeling, and mold. Based on the Pareto diagram, the most dominant defects are peeling (56.68%) and breakage (41.12%). The p-chart analysis shows that the production process is not yet statistically stable. Furthermore, the cause-and-effect diagram identifies several key causes of defects, including dirty storage rooms, high temperature and humidity, unpredictable weather conditions, inappropriate tools, inconsistent and contaminated materials, frequent tossing of incense sticks, as well as employee discomfort and fatigue. Based on these findings, recommended improvements include controlling room temperature and humidity, using closed containers, developing standardized drying SOPs, implementing work rotation, increasing rest periods to reduce fatigue, and enhancing raw material selection and sorting before production.